2017
DOI: 10.1002/adma.201703787
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Protein Biomarkers with Organic Electrochemical Transistors

Abstract: The analysis of protein biomarkers is of great importance in the diagnosis of diseases. Although many convenient and low-cost electrochemical approaches have been extensively investigated, they are not sensitive enough in the detection of protein biomarkers with low concentrations in physiological environments. Here, this study reports a novel organic-electrochemical-transistor-based biosensor that can successfully detect cancer protein biomarkers with ultrahigh sensitivity. The devices are operated by detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
173
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(174 citation statements)
references
References 41 publications
(38 reference statements)
0
173
0
1
Order By: Relevance
“…The electrical double layer is the result of the variation of electrical potential near the surface [54]. Reproduced from [49] with permission from Willey . Polyion complex membrane prepared from oppositely charged polyelectrolytes has been successfully used as effective molecular recognition interfaces for sensor construction.…”
Section: Electrochemical Immunosensor For Detection Protein Biomarkermentioning
confidence: 99%
“…The electrical double layer is the result of the variation of electrical potential near the surface [54]. Reproduced from [49] with permission from Willey . Polyion complex membrane prepared from oppositely charged polyelectrolytes has been successfully used as effective molecular recognition interfaces for sensor construction.…”
Section: Electrochemical Immunosensor For Detection Protein Biomarkermentioning
confidence: 99%
“…f) The sensing mechanism of the OECT‐based biosensors for detecting HER2. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Integration Of Biomacromolecules Into Otft‐based Sensorsmentioning
confidence: 99%
“…The rapidly developing immunosensors (antibody–antigen sensors) have been actively applied in such fields as food, industry, environmental monitoring, and clinical examinations due to their high specificity, sensitivity, and stability . Lee et al first demonstrated PEDOT:PSS‐based OECTs for prostate specific antigen (PSA) detection .…”
Section: Integration Of Biomacromolecules Into Otft‐based Sensorsmentioning
confidence: 99%
See 2 more Smart Citations